2014
DOI: 10.1186/1478-4505-12-61
|View full text |Cite
|
Sign up to set email alerts
|

Public reporting improves antibiotic prescribing for upper respiratory tract infections in primary care: a matched-pair cluster-randomized trial in China

Abstract: BackgroundInappropriate use and overuse of antibiotics is a serious concern in the treatment of upper respiratory tract infections (URTIs), especially in developing countries. In recent decades, information disclosure and public reporting (PR) has become an instrument for encouraging good practice in healthcare. This study evaluated the impact of PR on antibiotic prescribing for URTIs in a sample of primary care institutions in China.MethodsA matched-pair cluster-randomized trial was undertaken in QJ city, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 41 publications
0
89
0
Order By: Relevance
“…A previous study of patients with upper respiratory tract infections29 found a significant reduction in combined use of antibiotics as a result of a four-month reporting intervention; but no changes in injection prescriptions were observed. These results are similar to our findings in this study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A previous study of patients with upper respiratory tract infections29 found a significant reduction in combined use of antibiotics as a result of a four-month reporting intervention; but no changes in injection prescriptions were observed. These results are similar to our findings in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Unlike previous efforts made by Yang’s29 and Wang’s30 teams, where the impact of public reporting on prescriptions was examined through a single disease condition (upper respiratory tract infections) or using a single prescribing indicator (percentage of prescriptions containing injections) over a short period of time (4 months), this study evaluated the impact of public reporting on the use of antibiotics and injections for a range of conditions over a relatively longer period of time (1 year). We chose three conditions for the purpose of this study: bronchitis, gastritis and hypertension.…”
mentioning
confidence: 85%
“…The intervention hospital translated the policies into a local AMS programme through training for doctors on guidelines, prescription review and restricting non‐compliant doctors – which may be associated with reduced APR for outpatients. We knew that limited administrative measures, such as posting individual doctor's APRs publicly, were ineffective . This has to be a combined effort.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to emphasizing the importance of process measures, several studies stressed the significance of patient education during public reporting. Yang indicated that consumer education was required to maximize the impact of public reporting [27]. Stephanie et al suggested that education was required to help assist patients interpret quality data, and an improved public education on quality data was required to increase the use of reporting data in the future [28].…”
Section: Discussionmentioning
confidence: 99%